2014
DOI: 10.1038/srep05136
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the vaginal Lactobacillus microbiota associated with preterm delivery

Abstract: The presence of an abnormal vaginal microflora in early pregnancy is a risk factor for preterm delivery. There is no investigation on vaginal flora dominated by lactic acid bacteria and possible association with preterm delivery. We assessed the dominant vaginal Lactobacillus species in healthy pregnant women in early pregnancy in relation to pregnancy outcome. We observed 111 low risk pregnant women with a normal vaginal microflora 11 + 0 to 14 + 0 weeks of pregnancy without subjective complaints. Vaginal sme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
127
8
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(160 citation statements)
references
References 40 publications
8
127
8
9
Order By: Relevance
“…Furthermore, several previous studies showed that prepregnancy body mass index (BMI) and plasma leptin levels may influence the outcomes of pregnancies, such as preterm delivery, low-birth-weight infants, macrosomia, and delivery disorders (12,13). These obstetric and neonatal disorders were also associated with Lactobacillus inersdominant microbiota in early pregnancy and the presence of bacteria related to bacterial vaginosis, as detected by vaginal smears (8,(14)(15)(16). To the best of our knowledge, no study to date has examined the relationship between obesity and Lactobacillus composition in the reproductive tract.…”
mentioning
confidence: 81%
See 2 more Smart Citations
“…Furthermore, several previous studies showed that prepregnancy body mass index (BMI) and plasma leptin levels may influence the outcomes of pregnancies, such as preterm delivery, low-birth-weight infants, macrosomia, and delivery disorders (12,13). These obstetric and neonatal disorders were also associated with Lactobacillus inersdominant microbiota in early pregnancy and the presence of bacteria related to bacterial vaginosis, as detected by vaginal smears (8,(14)(15)(16). To the best of our knowledge, no study to date has examined the relationship between obesity and Lactobacillus composition in the reproductive tract.…”
mentioning
confidence: 81%
“…An abnormal vaginal microflora in pregnant women is a risk factor for preterm delivery, and the dominance of L. iners in vaginal smears from healthy women during early pregnancy is associated with preterm delivery (8,14). Women with large proportions of L. crispatus had high Escherichia coli inhibitory activity, whereas women whose vaginal smears were dominated by L. iners had low E. coli inhibitory activity (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…have shown that women with Lactobacillus iners have a greater risk of preterm delivery than women with other types of lactobacillus spp. [16]. He has also shown that different lactobacillus can restore the vaginal flora after antibiotic treatment of BV [17].…”
Section: Figurementioning
confidence: 99%
“…Это при-водит к размножению анаэробов, ассоцииро-ванных с БВ. Таким образом, преобладание L. iners часто наблюдается в переходный этап между нормальным состоянием влагалищного микробиоценоза и нарушенным и может пред-располагать к развитию патогенной влагалищ-ной микрофлоры, что, в свою очередь, может быть потенциально связано с невынашивани-ем беременности и преждевременными родами [15,16,20].…”
Section: вагинальный микробиомunclassified